Comparative Analysis of the Financial Performance of Rambusaratu Village Before and During the 2018-2020 Covid-19 Pandemic - Muliana; Novia Sandra Dewi (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The purpose of this study was to determine the financial performance of Rambusaratu Village before and during the 2018-2020 Covid-19 Pandemic using the independence ratio, effectiveness ratio, efficiency ratio, and growth ratio. This type of research is a quantitative descriptive research using secondary data in the form of reports on the realization of the Village Revenue and Expenditure Budget (APBDes) for Rambusaratu Village for 2018-2020. The data analysis technique in this study uses the formula for the independence ratio, the effectiveness ratio, the efficiency ratio, and the growth ratio. The results showed that the financial performance of Rambusaratu Village based on the independence ratio was high with an average ratio of 100%, because Rambusaratu Village did not depend on assistance from the provincial and district/city governments. Based on the effectiveness ratio, the financial performance is categorized as effective with an average ratio of 100%, because the realization of the budget is in accordance with the target to be achieved. From the efficiency ratio, it was found that financial performance was less efficient with an average ratio of 100%, this was because the Village had not been able to suppress the amount of the expenditure budget, and the growth ratio showed that finance had increased and decreased every year.